2020
DOI: 10.1111/1475-6773.13307
|View full text |Cite
|
Sign up to set email alerts
|

State earned income tax credits and general health indicators: A quasi‐experimental national study 1993‐2016

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…This relationship was also observed using a continuous version of the state earned income tax credit variable; however, no association was found for nonrefundable state earned income tax credit laws. Inability to detect a statistically significant relationship between HIV risk behavior and non-refundable state earned income tax credit laws may reflect a decreased likelihood of accessing these credits due to the lower average level of tax liability among this population [15]. Likewise, a refundable credit less than 10% of the FEITC (FEITC = $6431 for a family with 3 or more children in 2018) may not be large enough to have a meaningful impact on HIV risk behavior for lowincome single mothers [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This relationship was also observed using a continuous version of the state earned income tax credit variable; however, no association was found for nonrefundable state earned income tax credit laws. Inability to detect a statistically significant relationship between HIV risk behavior and non-refundable state earned income tax credit laws may reflect a decreased likelihood of accessing these credits due to the lower average level of tax liability among this population [15]. Likewise, a refundable credit less than 10% of the FEITC (FEITC = $6431 for a family with 3 or more children in 2018) may not be large enough to have a meaningful impact on HIV risk behavior for lowincome single mothers [19].…”
Section: Discussionmentioning
confidence: 99%
“…The ≥ 10% FEITC reflects the 75th percentile of state earned income tax credit generosity for our study population. The "refundable" designation is important to consider in variable construction given that non-refundable tax credits are less available to this low-earning population that typically does not carry substantial tax liability [15]. We use a 1-year lagged version of the state earned income tax credit variable to reflect the fact that the question on HIV risk behavior references behavior over the prior year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several years, CDC supported studies showing how economic supports for families and the promotion of family-friendly work policies are effective in reducing or mitigating ACEs ( Appendix Table 2 , available online). In particular, studies found significant associations between state EITCs, 65 68 federal child tax credits, 69 state Medicaid expansions, 70 maternal homeownership, 71 and paid parental leave policies 72 on decreases in CAN and other ACEs.…”
Section: Centers For Disease Control and Prevention Investments In Re...mentioning
confidence: 99%
“…We found that more generous state EITCs were associated with reduced rates of child maltreatment and adult mental distress, particularly among those with lower educational attainment, who are more likely to receive the EITC. 6,7 There is still much to learn about how best to use income support as a health intervention. We hope current and future researchers will be inspired by Shafer et al 1 to study the CTC and other innovations in income support over time and in relation to multiple domains of child and adult health.…”
Section: + Related Articlementioning
confidence: 99%